Holier than Thou: A Comparative Study of Leader-Member Exchange (LMX) Effectiveness in Transactional and Transformational Leadership in IT Companies - M. Ikhwan Maulana Haeruddin; Agung Widhi Kurniawan; Abdi Akbar; Burhanuddin Burhanuddin; Tenri Dipoatmodjo; Muhammad Yushar Mustafa (Jurnal Ad'ministrare, 2021)
This research aims to explore the effectiveness of transactional and transformational leadership style in creating effective Leader-Member Exchange relationship in organization, particularly in IT companies. The research was carried out in the Indonesia during the year of 2020. Semi-structured interviews were conducted on 149 respondents over a period of 12 months between February 2020 and November 2020 in 119 IT companies located in major cities of Indonesia. The results of this study indicate that the transformational leadership is more holistic than transactional leadership. In developing high-quality leader – member relationship, personal touch of a leader is needed to inspire his/ her followers to perform beyond expectations and sacrifice to surpass their self-interests for organizational interests. Moreover, to create a warmer and friendlier work atmosphere a leader should be more aware of the out-group existence and he/she supposes to build a relationship reciprocally not based on personal preferences, but rather based on the recent and future potential, and also assigns tasks to those who have skill and readiness. The challenge of this paper is that difficult to generalize the result as this paper approaches the problems by a qualitative stance. This paper contributes to the exiting literatures on how effective transformational leadership in generating high quality leader – member relationships in order to influence member’s job performance and job satisfaction in an organization.